Dissection of fertility barriers among lineages of Gibberella zeae - Fuentes-Bueno, Irazema (Kansas State University, 2012)
Fusarium graminearum Schwabe sensu lato (teleomorph: Gibberella zeae (Schwein.) Petch), a homothallic ascomycete fungus, is the causal agent of Fusarium head blight (FHB) of wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), and other small grains. FHB occurs worldwide and serious outbreaks have been reported in North America, South America, Asia, and Europe. According to the phylogenetic species concept (PSC), F. graminearum is composed of at least 15 phylogenetic lineages known as the Fusarium graminearum species complex. Although F. graminearum is homothallic, some members of different phylogenetic lineages are known to intercross in the laboratory. It has been suggested that F. graminearum sensu lato fits the biological species concept (BSC). According to the BSC, “species are groups of actually or potentially interbreeding natural populations, which are reproductively isolated from other such groups”. Previous reports of intercrossing were qualitative, so the degree of reproductive isolation, if any, is not clear. Since intrinsic reproductive isolation is the key criterion to identify species by the BSC, more detailed quantitative information is needed. Chromosome rearrangements between fungal strains may reduce fertility in sexual crosses through the production of genetically inviable recombinant progeny. As such, rearrangements can be important postzygotic reproductive barriers between species. Following methods used in Neurospora crassa, ascospore tetrads were analyzed for patterns of ascospore viability. Crosses were made with three lineage 7 (F. graminearum sensu stricto according to PSC) strains as female. Each female was a MAT1-2 knockout mutant that rendered it obligately heterothallic. Males were several members of lineages 6 (F. asiaticum according to PSC) and lineage 7. Crosses with lineage 7 males formed complete asci with 8 ascospores indicating that their genomes are isosequential with the testers. Crosses with one strain from lineage 6 with two known inversions produced asci containing 8, 6, and 4 ascospores, consistent with it not being isosequential. However, three other strains of lineage 6 appeared to be isosequential with the testers. Therefore, chromosome rearrangements did not appear to be common to strains of lineage 6 and probably do not contribute significantly to reproductive isolation of lineage 6 and lineage 7. Interlineage fertility studies with the three lineage 7 tester strains were performed to quantify interlineage fertility parameters including the total number of ascospores produced, perithecial density, and perithecium internal development scores. All lineage 7 female testers successfully crossed to all 23 male strains from lineages 1 to 9. For total ascospore production, one female tester crossed equally well with all lineages and the other two testers showed statistically significant differences for a few lineages. For perithecial density, there was a significantly lower density with all three testers when crossed with lineage 6, but the other lineages were not statistically different from lineage 7. For perithecial development, there was large variation for every lineage. Therefore, in the crosses with reduced fertility, the reduction can be attributed to a postzygotic effect since mature perithecia and asci developed. All of the tested lineages of the Fusarium graminearum species complex can produce viable progeny with F. graminearum lineage 7, which was the taxonomic type of the original species before it was split into phylogenetic species. There are a few examples of reduced fertility with two lineage 7 testers, the remaining tester crossed equally well with all lineages. Therefore members of lineages 1-9 all should be considered members of Fusarium graminearum according to the BSC. The existing female testers could be used to identify members of the F. graminearum clade by performing test crosses in the laboratory. The PSC and BSC species concepts do not agree for this group of fungi. This disagreement indicates that the F. graminearum species complex is in the early stages of speciation. The lack of intrinsic reproductive barriers supports the hypothesis that these lineages have developed in geographic isolation. As the lineages have apparently been brought together through global trade, interlineage hybrids have been reported in the field. The discrepancy between PSC and BSC will eventually be resolved by whether the lineages fuse or remain separate in nature. Even if the lineages remain separate, this study demonstrates the potential for gene flow between lineage 7 and lineages 1 through 9.
Keywords: Fusarium graminearum; Gibberella zeae; Fusarium graminearum species complex; Reproductive isolation; Interlineage fertility; Biological species concept; Phylogenetic species concept; Plant Pathology (0480)